Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Minat Beli Konsumen di Okui Kopi 3.0 Surabaya - Rizki Ivah Lutfiah; Sri Widayanti; Sri Tjondro Winarno (Universitas Merdeka Madiun, 2021)
The purpose of this study aims to determine the 7P marketing mix activities carried out by Okui Kopi 3.0 Surabaya on consumer purchase interest, to determine the effect of the 7P marketing mix on consumer purchase interest, and to imply the results of research for Okui Kopi 3.0 Surabaya shop. The sampling method used was a non-probability sampling method with a purposive sampling technique. The number of samples in this study were 50 respondents. The data analysis technique used was the Structural Equation Model Partial Least Square (SEM PLS). The results of this study indicate that the variables of product, price, place, promotion, and people have a significant influence on consumer buying interest where the p-value is ≤ 0.05. Meanwhile, process variables and physical evidence did not have a significant effect on consumer purchase interest because the p-value > 0.05. Keywords—: Marketing Mix, Consumer Purchase Interest, SEM-PLS, Okui Kopi 3.0 Surabaya.